Jagung Katemak, Makanan Tradisional Khas Pulau Timor Barat, Nusa Tenggara Timur - Witoyo, Jatmiko Eko; Naisali, Hyldegardis; Utoro, Panggulu Ahmad Ramadhani; Hamaisa, Atika (Agriculture Faculty of Flores University, 2024)
West Timor Island is one of the islands in East Nusa Tenggara Province, which has a dry climate and rocky geographical area, with corn as the main commodity. Corn is a staple food and ingredient to produce various traditional ethnic foods. “Jagung katemak” is one of the traditional ethnic foods made from local corn combined with various vegetables, legumes, and other spices, using simple methods and paying attention to local wisdom. However, a comprehensive and in-depth exploration of its history, constituent composition of ingredients, and the traditional processing of “jagung katemak” is still infrequent. This paper aims to uncover the history, composition of ingredients, and the traditional processing of “jagung katemak” from various sources, including books, scientific journals, and local news relevant to the topic discussed. The study's results show that the history, composition of ingredients, and traditional processing of “jagung katemak” have been successfully revealed in detail and depth. In addition, the challenges and prospects of developing katemak corn in the contemporary era are also comprehensively reviewed. Hopefully, “jagung katemak” can be nationally and internationally recognizable by highlighting local wisdom.